Guidance hypothesis with verbal feedback in learning a palpation skill. - Pringle RK (Journal of Manipulative & Physiological Therapeutics, 2004)
OBJECTIVE: To investigate whether a force application of a novel motor skill was simple or complex and to determine the appropriate level of feedback during training. The objective was to determine the effects of various amounts of knowledge of results (KR) on learning a novel skill that is frequently taught in chiropractic for the assessment of vertebral motor unit dysfunction. METHODS: Thirty-five active subjects were taught the novel skill of spring testing to a particular force range through 9 or 10 teaching sessions over a 2-week period (a school holiday limited some to only 9 sessions). To determine the particular force range, an initial phase of the study involved a licensed and practicing clinician performing motion palpation spring testing of the thoracic spine of a prone subject. The data from a total of 47 pushes throughout the thoracic spine were recorded, and the mean force and standard deviation were calculated. The second phase of the study used the obtained mean and standard deviation for teaching the force of prone thoracic spine motion palpation to 35 active subjects by administering spring testing to 35 passive subjects. The active subjects were randomly divided into 4 groups, with each receiving a varying amount of verbal feedback to move toward the target force of their learned skill. Each passive subject was laid prone on an instrumented adjusting table. Group 1 received the least amount of feedback while learning the novel skill. Groups 2 and 3 received more frequent, intermittent feedback while learning the skill, and group 4 received constant, frequent feedback during each of the 10 teaching sessions. All subjects returned within 2 weeks for 2 retention trials to determine the efficacy of the learned skill. RESULTS: The mean force determined was 143 N with a standard deviation of 14 N. Each subject was taught spring testing within this target range. The 2 final retention trials showed group 3 to have demonstrated the most targeted retention of the learned motor skill. These subjects exhibited the closest force range to the target for the motor skill learned and fewer changes in standard deviation compared with their acquisition trials and thus the highest retention. Group 4, receiving 100% feedback, demonstrated the most accurate spring testing during the acquisition trials, but the subjects did not effectively demonstrate when compared on acquisition and retention trials. CONCLUSION: The results of this study show data to be consistent with the guidance hypothesis in learning a novel motor skill. The constant KR feedback is beneficial for learning when used to reduce error during practice but detrimental when relied upon for retention and learning. These data suggest the necessity of using motor skill development learning theory in the teaching of chiropractic.